Adults' experiences of living with pulmonary hypertension: a thematic synthesis of qualitative studies. Issue 12 (7th December 2020) - Rawlings, Gregg Harry; Beail, Nigel; Armstrong, Iain; Condliffe, Robin; Kiely, David G; Sabroe, Ian; Thompson, Andrew R
Abstract : Objectives: Pulmonary hypertension is a life-shortening disease that has a considerable impact on quality of life. Improving our understanding of how individuals are affected and cope with the disease will help to improve services and outcomes. This review synthesises the published qualitative research that has listened to adults discuss their experiences of living with the disease. Design: A comprehensive systematic search of four databases was conducted in May 2020: Web of Science, PubMed, PsycINFO and Cochrane Library. Suitable studies were evaluated using the Critical Appraisal Skills programme. Findings from the studies were extracted and subjected to a thematic synthesis. Results: Nineteen articles were identified reflecting the experiences of over 1900 individuals impacted by pulmonary hypertension from Europe, North and South America and Asia. Ten studies did not report participant's WHO functional class of pulmonary hypertension, which resulted in comparing experiences between different severity difficult. All studies met the majority of the quality assessment items. Six descriptive themes emerged discussing participant's experiences of diagnosis, treatment, prognosis, healthcare professionals, impact and coping with pulmonary hypertension. Four higher order analytical themes were developed from the descriptive themes, reflecting: (i) uncertainties and anxiety that participants encountered related to pulmonary hypertension; (ii) lack of recognition of the impact of the condition; (iii) frustration at the paucity of awareness of pulmonary hypertension in society and healthcare settings and (iv) participant's accounts of transitioning through different stages of living with the disease. Conclusions: These findings form the first synthesis of experiences of life in individuals impacted by pulmonary hypertension and illustrate the multifaceted impact of the condition. The voices of numerous groups are missing from the literature highlighting the need for additional research. The results have implications for clinical practice emphasising the role of educational and psychological therapies to support those with the disease.